Features of the reproductive setting of men and women which are patients of the programs of assisted reproductive technologies (ARTs) - A. V. Kaminsky (Kazimierz Wielki University, 2017)
Infertility refers to those states that significantly affect the psycho-emotional status of a person, causing the state of chronic stress. In turn, chronic stress can lead to the development of stress-induced infertility. The aim of the study was to identify features of the reproductive setting of men and women who are patients of assisted reproductive technology (ART) programs in connection with reproductive behavior. Material and methods. Under supervision, there were 233 women and men who needed infertility treatment using ART methods, and 142 fertile women and men who had already had births, and applied for pre-gestational preparation before planning another pregnancy. Methods of psychological testing are used. Results. It has been established that the reproductive setting of infertile men and women is uncertain (contradictory); in it there is a discrepancy and ambivalence in the content of affective, cognitive and conative components. Reproductive testing of individuals having children is definite (harmonious); there is consistency in the content of affective, cognitive and conative components. There are gender differences in the components of the reproductive setting, both infertile and those with children. There is a connection between the type of reproductive setting and the personality characteristics, the relation to the spouse, the motives for the birth of the child. Conclusions. The reproductive settings of infertile men and women who are patients of the ART are different from those of mothers and fathers with newborn babies and require psychological correction.